DISCOURSE MARKERS AND LOGICAL CONNECTORS AS MEANS OF TEXTUAL COHERENCE IN MODERN ENGLISH AND UZBEK JOURNALISM (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
This article investigates the use and translation of discourse markers and logical connectors as means of textual coherence in modern English and Uzbek journalism. Based on a qualitative comparative analysis of parallel journalistic texts, the study examines how discourse markers are rendered in translation and identifies major translation strategies, including retention, substitution, omission, and addition. The findings demonstrate that discourse markers undergo systematic modification due to structural, stylistic, and cultural differences between the two languages. The study highlights the importance of functional equivalence and discourse-level adaptation in achieving coherence and communicative effectiveness in media translation.